2020
DOI: 10.3390/jcm9051536
|View full text |Cite
|
Sign up to set email alerts
|

Oral Iron for IBD Patients: Lessons Learned at Time of COVID-19 Pandemic

Abstract: Anemia is a frequent manifestation in patients with chronic inflammatory bowel disease (IBD) and requires tight monitoring and adequate supplementary therapy. Intravenous iron is the first-line treatment in subjects with moderate–severe anemia, active disease, or oral iron intolerance. On the other hand, oral iron is recommended in patients with mild anemia and inactive disease. However, during the current coronavirus pandemic, hospital activities have significantly changed, and all non-essential procedures, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Regarding the COVID-19 context, iron metabolism is clearly disrupted in SARS-CoV-2 infected patients, especially in subjects hardest hit by the disease [ 122 ], consequently anemia [ 123 ] or hyperferritinemia are typical manifestations of hospitalized COVID-19 patients. Therefore, optimal iron status may be crucial for better disease prognosis.…”
Section: Association Between 10 Critical Micronutrients and Prevalmentioning
confidence: 99%
“…Regarding the COVID-19 context, iron metabolism is clearly disrupted in SARS-CoV-2 infected patients, especially in subjects hardest hit by the disease [ 122 ], consequently anemia [ 123 ] or hyperferritinemia are typical manifestations of hospitalized COVID-19 patients. Therefore, optimal iron status may be crucial for better disease prognosis.…”
Section: Association Between 10 Critical Micronutrients and Prevalmentioning
confidence: 99%
“…However, this study was not a direct comparison to other iron formulations, patients were only included if their disease was in remission or non-severe and if they had previously failed treatment with other oral ferrous formulations [ 35 , 36 ]. Further studies have confirmed an acceptable safety profile for ferric maltol, demonstrating good tolerability and the majority of patients had Hb normalisation within 3 months [ 3 ]. Howaldt et al also demonstrated greater improvements in short form (SF-36) and mental component summary (MCS) scores with ferric maltol over IV iron, suggesting a greater improvement in quality of life [ 37 ].…”
Section: Managementmentioning
confidence: 99%
“…The advantages of oral iron include a well-established safety profile, its ease of route of administration and reduced cost [ 3 ]. In addition, oral iron is not associated with reduced productivity [ 41 ].…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations